Association between dynamic asymmetry of the newborn's head and intrauterine factors Associação entre a assimetria dinâmica da cabeça do recém-nascido e fatores intra-uterinos - Cláudia Regina Beuter; Fleming Salvador Pedroso; Ricardo César Mazetto; Cassandra Trojahn dos Santos; Ângela Garcia Rossi (Arquivos de Neuro-Psiquiatria)
A non-comparable, individual, observational and contemporary cross-sectional study in newborns was made to determine the dynamic lateralization in the head turning after release from the midline and its relationship with obstetric variables. From October to December of 2005, 320 newborns were admitted to the Adjacent Lodgings of the University Hospital of Santa Maria. From those, 89 were selected for assessment of the vestibular function since they have had previously fetal static control through ultrasound. Our results show that the right-sided head lateralization was significantly greater than the left-sided. The predominancy of the lateralization towards the right side also occurred in cephalic presentations and left-sided back, however these were not significant. Results corroborate with the existing literature and suggest an association between fetal static and vestibular function. Com o objetivo determinar a lateralização dinâmica na prova da queda da cabeça e sua associação com variáveis obstétricas, foi realizado um estudo transversal no recém-nascido, não comparado, individual, observacional e contemporâneo. No período de outubro a dezembro de 2005, 320 recém-nascidos foram admitidos no Alojamento Conjunto do Hospital Universitário de Santa Maria, e destes 89 foram selecionados para avaliação da função vestibular, por terem feito controle da estática fetal através do ultrasom. Nossos resultados mostram que a lateralização da cabeça para a direita foi significativamente maior do que para esquerda. Também este predomínio da lateralização para a direita ocorreu nas apresentações cefálicas e com o dorso para esquerda, no entanto estes não foram significativos. Nossos resultados corroboram com a literatura existente, e sugerem uma associação entre a estática fetal e a função vestibular.